Ekstrak Keladi Tikus (Typhonium flagelliforme) Fraksi Diklorometanolik dan Ekspresi Caspase-3 dan p21 Cell-Line Kanker Payudara MCF-7 - Agung Putra; Tjahjono Tjahjono; Winarto Winarto (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTThe dichloromethanolic fraction of keladi tikus (Typhonium flagelliforme) extract and the expression of p21 and caspase-3 of MCF-7 breast cancer cell-lineBackground: Breast cancer has a high degree of heterogeneity and problems in therapy, such as insensitive to antiproliferation signal and able to escape from apoptosis program. Typhonium flagelliforme (Lodd), Blume (Araceae) more commonly known as keladi tikus in Indonesia, often used as alternative in treating cancer, including breast cancer. The objective of study is proving the dichloromethanolic fraction of Typhonium flagelliforme tuber extracts influence on the expression of caspase-3 and p21 of MCF-7 cell-line that have deletion in CASP-3 gene.Methods: This study adapts laboratory experimental in-vitro in cells-line MCF-7, with “post test control group only design” and divided into two groups, were incubated in 5h, 10h and 20h. The control group received no other treatment. The treatment group received the dichloromethanolic fraction of Typhonium flagelliforme tuber extracts in IC50. Starting with cytotoxicity assay using MTT to determine the IC50, followed by Immunocytochemical analysis to observe the expression of p21 and caspase-3.Results: Paired sample T test shows a significant differences in treatment groups compared with the controls (p<0.05), namely an increase in the expression of nuclear p21 and caspase-3 on 20h incubation.Conclusion: There were increased in the expression of caspase-3 and nuclear p21, as well as depleted the cytoplasmic of p21 on MCF-7 cell-line that have deletion in CASP-3 in treatment by tuber extract of Typhonium flagelliforme dichloromethanolic fraction.Keywords: p21, caspase-3, MCF-7 cell-line, Typhonium flagelliformeABSTRAKLatar belakang: Kanker payudara mempunyai tingkat heterogenitas tinggi dan problem dalam terapi, diantaranya tidak sensitif terhadap signal antiproliferasi dan mampu menghindar dari program apoptosis. Typhonium flagelliforme (Lodd). Blume (Araceae) yang lebih dikenal sebagai keladi tikus di Indonesia, sering digunakan sebagai alternatif dalam mengobati penyakit kanker,termasuk kanker payudara. Tujuan penelitian ini untuk membuktikan pengaruh Typhonium flagelliforme terhadap ekspresi caspase- 3 dan p21 pada cell-line MCF-7 yang mengalami delesi gen CASP-3.Metode: Penelitian eksperimental laboratorik secara invitro pada cell-line MCF-7, dengan rancangan penelitian post test control group only design, yang dibagi dalam 2 kelompok dan diinkubasi dalam 5 jam, 10 jam dan 20 jam. Kelompok kontrol tidak mendapatkan perlakuan, sedangkan kelompok perlakuan mendapatkan ekstrak umbi Typhonium flagelliforme fraksi diklorometanolik kadar 62,08 μg/mL(IC50). Dimulai dengan uji sitotoksisitas menggunakan MTT untuk menentukan IC50, dilanjutkananalisis imunositokimia untuk melihat ekspresi p21 dan caspase-3.Hasil: Paired sample T test menunjukkan terdapat perbedaan bermakna pada kelompok perlakuan dibandingkan kontrol (p<0,05), dimana terjadi peningkatan ekspresi caspase-3 dan p21 nukleus serta deplesi p21 sitoplasmik pada inkubasi 20 jam.Simpulan: Ekstrak umbi Typhonium flagelliforme fraksi diklorometanolik mampu meningkatkan ekspresi caspase-3 dan p21 nukleus serta deplesi p21 sitoplasmik cell-line MCF-7 yang mengalami delesi gen CASP-3.